2012
DOI: 10.3109/03009734.2011.650796
|View full text |Cite
|
Sign up to set email alerts
|

Experimental sepsis in pigs—effects of vasopressin on renal, hepatic, and intestinal dysfunction

Abstract: IntroductionLow-dose arginine vasopressin (AVP) has been proposed as an adjunctive vasopressor for the treatment of advanced vasodilatory shock. However, its effects on renal, hepatic, and intestinal dysfunction during sepsis remain controversial.MethodsFecal peritonitis was induced in 20 anesthetized, invasively monitored, mechanically ventilated female pigs. Following the time point of septic shock (defined as mean artery pressure (MAP) ≤65 mmHg), animals were randomly assigned to the following groups (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…Others have used models of isolated hollow viscous injury, 15 16 or attempted to replicate Gram-negative sepsis with endotoxin infusion. 17 While these models do create uncontrolled intra-abdominal sepsis, there is no transition to a period of source control that would be clinically realistic.…”
Section: Discussionmentioning
confidence: 99%
“…Others have used models of isolated hollow viscous injury, 15 16 or attempted to replicate Gram-negative sepsis with endotoxin infusion. 17 While these models do create uncontrolled intra-abdominal sepsis, there is no transition to a period of source control that would be clinically realistic.…”
Section: Discussionmentioning
confidence: 99%
“…VA group) also tended to cause higher troponin I concentrations in systemic blood, but the difference did not attain statistical significance as only half of the animals had very high troponin I values, and transiently greater protein S-100β levels in jugular venous blood, implying a tendency towards greater cerebral and cardiac injury. This might explain the post-resuscitation myocardial dysfunction observed after adrenaline administration during CPR ( 37 ) in contrast to the beneficial visceral effects of the vasopressin-noradrenaline combination observed ( 38 ) in experimental septic shock. In addition, cerebral cortical blood flow (CCBF) was numerically (36%) higher after ROSC in the V group, indicating difficulties in maintaining cerebral perfusion after ROSC in the VA group.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous small noncontrolled trials using vasopressin for the treatment of hypotension in septic patients since the first report of its success by Landry et al An example of 1 such trial examined 24 human patients with septic shock that were given a low dose of vasopressin (median 0.06 U/min) and found that their dose of norepinephrine could be decreased while the mean arterial blood pressure and cardiac index were maintained . This finding has also been seen in an experimental, randomized porcine peritonitis septic shock model . The administration of vasopressin was associated with a lower total norepinephrine and fluid requirement in order to maintain mean arterial pressure and pulmonary capillary wedge pressure in the target range.…”
Section: Introductionmentioning
confidence: 86%